Organizational behavior - Robbins, Stephen P.; Judge, Tim (Pearson, 2022)
"In this edition of Organizational Behavior, we build upon the basic core of OB knowledge to highlight timely advancements in these topics. Over half of the examples and references have been updated since the previous edition. We have completely revisited, revised, and refreshed the chapters on Diversity and Inclusion, Communication, Organizational Culture and Change, and Organizational Health and Stress to meet these current learning and teaching challenges"--Provided by publisher.